Pengaruh Upah, Pertumbuhan Ekonomi, dan Pendidikan Terhadap Penyerapan Tenaga Kerja Provinsi Banten - Rahmatin, Nur Ihriza; Solekha, Sheptia Dwi Imroatus; Putri, Icha Kartika; Nilasari, Aprilia; Arisetyawan, Kukuh (Universitas Negeri Surabaya, 2024)
The aims of this study is to determine the effect of economic growth, minimum wage, and education on labor absorption in Banten Province in 2019-2023. The analysis was conducted using panel data regression with the Fixed Effect Model (FEM) approach. The results show that economic growth has a significant negative effect on labour absorption, while minimum wage has a negative but insignificant effect. In contrast, education has a positive and significant effect on labour absorption. The results also show that all independent variables in this study simultaneously have a significant effect on labour absorption.